Infrared and multi‐wavelength Raman spectroscopy of regio‐regular P3HT and its deutero derivatives. (1st December 2017) - Brambilla, L.; Capel Ferrón, C.; Tommasini, M.; Hong, K.; López Navarrete, J.T.; Hernández, V.; Zerbi, G.
Abstract: The recently synthesized regio‐regular poly(3‐hexylthiophene‐2, 5‐diyl) selectively deuterated on the main chain backbone and/or on the hexyl side chain have given the opportunity to record their infrared (IR) and Raman spectra, and to carry out a spectroscopic study supported by density functional theory calculations. The Effective Conjugation Coordinate associated with the collective C=C stretching mode, with Raman scattering and IR absorption near 1, 450 cm −1, is used as a probe of the electronic structure and the molecular conformation of the chain backbone. With the help of the data collected from the deuterated species, the vibrational assignment for the structurally relevant 1, 600–1, 300 cm −1 region has been clarified. The excitation‐dependent wavenumbers and intensities of the C=C stretching Raman modes are discussed. Raman spectra excited in‐resonance or off‐resonance show the existence of a multimodal distribution of effective conjugation lengths that are ascribed to a phase hairy‐A with a practically flat backbone chain, a phase hairy‐B where the conformation of the backbone is slightly distorted, and an amorphous phase. IR spectra provide additional information on the Effective Conjugation Coordinate. Abstract : Infrared and Raman measurements on selectively deuterated regio‐regular P3HT samples, supported by density functional theory models, improve the assignment of the spectra features observed between 1, 600 and 1, 300 cm −1 . The collective C=C stretching mode near 1, 450 cm −1, strong in Raman scattering and in infrared absorption, is used as a probe of the electronic structure and molecular conformations of the chain backbone. Three phases associated with different molecular structures are shown to exist in solid P3HT.